Explorative Study Of Emotional Fatigue Among Employees in Educational Institutions - Kusnani Sita Handayu; Anita Maharani; Kurnia Endah Riana (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study investigates the effect of role stress and job resources on emotional exhaustion, with work-family conflict as a mediating variable among higher education personnel. Employing a quantitative research design with a causality analysis approach, data were collected through a structured questionnaire using a five-point Likert scale. The sample consisted of 200 educational staff at XYZ institution in Bogor Regency, including civil servants, permanent employees, and contract workers. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique with SmartPLS 3 software. The findings revealed that role stress has a positive and significant impact on emotional exhaustion, indicating that increased stress from role demands contributes to higher levels of emotional fatigue. Conversely, job resources were found to have no significant direct effect on emotional exhaustion. Furthermore, work-family conflict significantly mediated the relationship between role stress and emotional exhaustion, suggesting that stress from conflicting work and family demands intensifies emotional exhaustion. However, work-family conflict did not mediate the relationship between job resources and emotional exhaustion. These results emphasize the critical need for effective stress management strategies and support systems that can help reduce work-family conflict to maintain the emotional well-being of education personnel. This study contributes to understanding the psychological dynamics in the workplace and provides insight into improving employee resilience and productivity in educational institutions.